Infant Mortality in Okinawa and Japan, 1973 - 2009 - Hokama, T.; Lee, Andy (Nova Biomedical Books, 2012)
Background: Infant mortality rate (IMR), defined as the number of infant deaths per 1000 live births, is a widely accepted indicator of the level of health and living standard in a country. After the Second World War, Japan has made substantial progress in reducing its IMR through regular maternal and infant health examination, as well as nutritional education for pregnant mothers. Okinawa, an island prefecture furthest from mainland Japan, experienced one of the highest IMR among all prefectures prior to 1973. Objective: To document the trend in IMR for Okinawa and all Japan and investigate the leading causes of infant death. Method: Infant mortality data from 1973 to 2009 were retrieved from the Okinawa Prefectural Government Office Report and the Maternal and Child Health Statistics of Japan. The main causes of infant death were obtained for the recent period 2005-2008. Results: IMR decreased from 14.S (Okinawa) and 11.3 (Japan) in 1973 to 2.4 in 2009. For Japan, the three leading causes of infant mortality were (I) congenital malformations, deformations and chromosomal abnormalities; (2) respiratory and cardiovascular disorders specific to perinatal period; and (3) sudden infant death syndrome, which together accounted for approximately 55% of all infant deaths during the period 2005-2008. For Okinawa, the total number of deaths was small (about 30 to 40 annually). Consequently, the rates for various causes were unstable, apart from the leading cause congenital malformations, deformations and chromosomal abnormalities Conclusion: Despite the relatively low per capita income, the Okinawa prefecture was successful in reducing its IMR to one of the lowest rate in the world. Implementation of a good health care system including universal health insurance and neonatal care contributed to this significant reduction over the past four decades.